Theater as Illusion: An Architectural Project in Kansas City - Marsha B. Hale (Oz, 1980)
The various levels of organization of the parts of this project presented some interesting difficulties. These parts, the auditorium, bar/restaurant, their supporting spaces had to be arranged on a very confined site which sloped slightly to the east…